Isolation and Characterization of a 32-kDa Fibrinolytic Enzyme (FE-32kDa) from Gloydius blomhoffii siniticus Venom - Kim Joung-Yoon; Lee Seung-Bae; Kwon Ki Rok; Choi Suk-Ho (Korean Pharmacopuncture Institute, 2014)
Objectives: This study was undertaken to isolate a fibrinolytic enzyme from the snake venom of Gloydius blomhoffii siniticus and to investigate its enzymatic characteristics and hemorrhagic activity as a potential pharmacopuncture agent. Methods: The fibrinolytic enzyme was isolated by using chromatography, sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and fibrin plate assay. The characteristics of the enzyme were investigated using fibrin plate assay, protein hydrolysis analysis, and hemorrhage assay. Its amino acid composition was determined. Results: The fibrinolytic enzyme with the molecular weight of 32kDa (FE-32kDa) from Gloydius blomhoffii siniticus showed a fibrin hydrolysis zone at the concentration of 0.2 mg/mL in the fibrin plate assay. The fibrin hydrolysis activity of the enzyme was inhibited completely by ethylenediaminetetraacetic acid (EDTA), ethyleneglycoltetraacetic acid (EGTA), and 1, 10-phenanthroline, thiothreitol and cysteine, and partially by phenylmethanesulfonylfluoride (PMSF). Metal ions such as Fe2+ and Hg2+ inhibited the fibrin hydrolysis completely, but Zn2+ enhanced it. FE-32kDa hydrolyzed α-chain but did not hydrolyze β-chain and γ-chain of fibrinogen. High-molecular-weight polypeptides of gelatin were hydrolyzed partially into low-molecular-weight polypeptides, but the extent of hydrolysis was limited. FE-32kDa induced hemorrhage beneath back skin of mice at the dose of 2 μg. Conclusions: FE-32kDa is a α-fibrin(ogen)olytic metalloprotease that requires Zn2+ for fibrinolytic activity and causes hemorrhage, suggesting that the enzyme is not appropriate for use as a clinical pharmacopuncture.